Air Pollution and Mental Disorders in Youth: An Epidemiological Assessment Integrating Nursing, Public Health, and Evidence-Based Nutritional Strategies - Alenazi, Menawer Sayaah Menawer; Alanazi, Hind Atallah Ramadan; Alanazi, Alhanoof Atallah Ramadan; Alharbi, Mona Abdulrhman Ali; Alshammari, Manal Khairallah A.; Mokeli, Ali Hamod Haidar; Homdi, Samer Alhassan Salwi; Alharbi, Essa Saad Mutlaq; Mawkili, Alhassan Hassan Arar; Refaei, Yahya Ali Mohammed; et al. (Journal of Posthumanism, 2024)
Background: The intersection of environmental epidemiology and pediatric psychiatry represents a critical frontier in modern public health. As urbanization accelerates and climate change intensifies, the global youth population is increasingly exposed to a complex "exposome" of atmospheric pollutants. Concurrently, the prevalence of mental health disorders among adolescents—specifically internalizing pathologies such as depression and anxiety—has reached crisis levels, with suicide remaining a leading cause of mortality in this demographic. While the respiratory and cardiovascular impacts of air pollution are well-documented, emerging evidence points to a "silent crisis" of neurotoxicity affecting the developing brains of adolescents. Objectives: This comprehensive systematic review aims to: (1) synthesize epidemiological data linking ambient and indoor air pollution (specifically PM2.5, NO2, and NOx) to internalizing (depression, anxiety, suicide) and externalizing (ADHD, conduct disorder) psychopathology in youth aged 10–24; (2) elucidate the biological mechanisms of neuroinflammation, oxidative stress, and HPA-axis dysregulation driving these outcomes; (3) evaluate the efficacy of school-based environmental interventions, such as HEPA filtration and green infrastructure; and (4) define the evolving role of school nurses in mitigation, surveillance, and advocacy within this environmental health framework. Methods: A systematic review of the literature was conducted, utilizing data from epidemiological cohorts, toxicological studies, and public health intervention trials. The search encompassed major databases (PubMed, Scopus, CINAHL) and grey literature from 2010–2023. Quality assessment was rigorous, utilizing the Newcastle-Ottawa Scale (NOS) for observational studies and the Cochrane Risk of Bias 2.0 (RoB 2.0) tool for randomized interventions. The review synthesizes findings from diverse geographical contexts, including high-exposure regions in Asia and varied exposure gradients in North America and Europe. Results: The synthesis reveals a robust, statistically significant association between exposure to particulate matter and nitrogen oxides and adverse mental health outcomes. Meta-analytic data suggests that long-term exposure to PM2.5 increases the odds of depression by approximately 10% per 10µg/m3 increase, with stronger effects observed in cumulative lag models. Short-term exposures are linked to immediate spikes in psychiatric emergency department visits (lags 0–3 days). Biologically, systemic inflammation (elevated IL-8, TNF-alpha) serves as a key mediating pathway. In the school setting, engineering interventions like HEPA filtration demonstrate a capacity to reduce indoor PM2.5 by 30-50%, correlating with improved cognitive function, reduced absenteeism, and potential behavioral benefits. Conclusion: Air pollution acts as a modifiable, pervasive environmental risk factor for youth mental health disorders. The evidence supports a paradigm shift in school nursing practice, moving beyond traditional somatic care to encompass "environmental mental health" surveillance. Integrated public health strategies—combining urban planning (Low Emission Zones), building engineering (filtration), nutritional resilience, and clinical vigilance—are essential to protect the neurodevelopmental trajectory of the next generation. The school nurse serves as the linchpin in this strategy, positioned to bridge the gap between environmental data and student well-being.